Reverse the Lens, Set Focus on the Followers: A Theoretical Framework of Resource Dependence, Upward Influence, and Leadership - Tripathi, Neha (Frontiers in Psychology, 2021)
Leadership theories predominantly focus on the top-down managerial influence on employees. Recent theoretical developments, however, have accentuated the call for scholarly attention on holistic models comprising both leadership and followership. In the present study, the author developed a theoretical framework of upward influence and leadership construction by drawing on resource dependence theory. Specifically, the author proposed a novel outlook illuminating upward influence in hierarchical relationships whereby employees, as the hosts of tacit resources, inculcate interdependent relationships with their managers. Considering the dependence of employees and managers on each other for tangible and intangible resources, relationships with a (a) power imbalance and (b) joint or embedded dependence emerge. The author further explained the role of leadership construction in power-imbalanced and embedded relationships and elaborated on organizational and team structural boundary conditions. By revitalizing upward influence, the proposed theoretical framework offered new insights into leadership and followership literature, with the potential to change the conversation from a foundational thesis assuming the managerial capacity to lead and bestow resources on their subordinates to a two-way resource-dependence perspective, which has been scarcely considered in contemporary management research.